2019
DOI: 10.1111/cid.12807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clinical local factors on thickness and morphology of Schneiderian membrane: A retrospective clinical study

Abstract: Background: It was informed that the thickness of maxillary sinus membrane may be affected by the local and patient-related factors in the literature.Purpose: The aim of this retrospective study is to evaluate factors that may have an influence of the thickness and morphology of the maxillary sinus membrane. Materials and Methods:A total of 414 cone beam computed tomography images of 207 patients were evaluated. Radiographic parameters were evaluated at each maxillary premolar and molar tooth regions. Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…[24] also measured the thickness of the maxillary sinus membrane and found that tooth vitality, residual alveolar bone height, and periodontal bone loss did not influence the thickness of the maxillary sinus membrane. Different from our study, the thickness of the membrane in each apical location was not shown in the study of Ramanauskaite et a l[24] Here we find that the thickness of membrane in each root apex differs significantly among roots from different people. Therefore, the thickness of membrane should be taken into account when assessing the risk before the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[24] also measured the thickness of the maxillary sinus membrane and found that tooth vitality, residual alveolar bone height, and periodontal bone loss did not influence the thickness of the maxillary sinus membrane. Different from our study, the thickness of the membrane in each apical location was not shown in the study of Ramanauskaite et a l[24] Here we find that the thickness of membrane in each root apex differs significantly among roots from different people. Therefore, the thickness of membrane should be taken into account when assessing the risk before the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the Schneiderian membrane on the CBCT scans was classified into five types according to previous reports 18 as follows: type I (healthy sinus membrane, no thickening), type II (flat sinus membrane, thickening without well‐defined outlines), type III (semispherical membrane, thickening with well‐defined outlines rising in an angle of >30° from the floor of the sinus walls), type IV (complete opacification of the sinus), and type V (mixed flat and semispherical thickenings) (Figure 5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…There was a statistically significant difference in the distribution of the mucosal thickness before and after surgery. The second method involves classification of mucosal morphology into five types 18 . In the double zygomatic implant group, the number of type IV cases was zero preoperatively and increased to six (13%) postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to sex, Dursun et al [26] conducted investigations on SMT due to the presence of teeth and showed that SMT was significantly higher in males compared to females. Ramanauskaite et al [30] also conducted investigations on SMT in the edentulous area and various local factors and showed that local factors like residual bone height and bone absorption were not correlated, but that males had a significantly higher thickness. Furthermore, Aksoy et al [31] conducted a similar investigation and showed that the rates of SMT > 2 mm in males and females were 52.8% and 35.9%, respectively, with males showing significantly higher thickness.…”
Section: Discussionmentioning
confidence: 99%